(untitled) (Medico Legal Update, 2019)
Background/Objectives: This study is descriptive survey study to factors influencing health conservation among middle age. Method/Statistical Analysis: The study subjects are 173 middle age who reside in M & C city area, and data-collection was done in period from March 05 to 23, 2018. The collected data was analyzed with Pearson’s correlation, multiple linear regression with stepwise method analysis. Findings: The result showed Health conservation was negatively correlated with fatigue and perceived stress, positively correlated with self-efficacy and social support. The major factors that affect health conservation in middle age were self-efficacy, social support, perceived stress, which explained 31.8% of health conservation. Improvements/Applications: The findings can provide the basis for the development of nursing interventions to improve health conservation.